2022
DOI: 10.1111/dth.15926
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of acquired reactive perforating collagenosis with dupilumab in a patient with end‐stage renal disease

Abstract: A 66-year-old man on peritoneal dialysis with a history of end-stage renal disease, hypertension, and type 2 diabetes presented with multiple severely pruritic hyperkeratotic nodules on the trunk and extremities (primarily on extensor surfaces), with an onset of several years previously. He had no history of atopic dermatitis. Laboratory tests revealed total immunoglobulin E in the normal range (27.1 IU/ml). Physical examination revealed erythematous papules and nodules, along with crateriform nodules, with ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Reports of six cases showed partial improvement of itch NRS as well as resolution of skin lesions under dupilumab treatment. Notably, three patients had no history of AD or atopy ( Table 2 ) [ 95 , 96 , 97 , 98 , 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…Reports of six cases showed partial improvement of itch NRS as well as resolution of skin lesions under dupilumab treatment. Notably, three patients had no history of AD or atopy ( Table 2 ) [ 95 , 96 , 97 , 98 , 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dupilumab, which is a fully human monoclonal antibody against interleukin‐4 receptor α (IL‐4Rα), effectively treats pruritic disorders. Our research group first reported the successful use of Dupilumab for the treatment of ARPC last year ( 12 ), subsequently, scholars from South Korea, Saudi Arabia, and Spain have also demonstrated therapeutic effects of dupilumab for ARPC ( 13 15 ), suggesting the involvement of Th2 inflammation in the pathophysiology of the disease.…”
Section: Introductionmentioning
confidence: 99%